DEVELOPMENT AND COMMISSIONING OF AN INNOVATIVE BIOREFINERY FOR THE CONVERSION OF CONTAMINATED BIOMASS INTO HIGH-QUALITY ENERGY CARRIERS - Kick, Christopher; Peetz, Pascal; Apfelbacher, Andreas; Meiller, M.; Daschner, Robert; Hornung, Andreas (European Biomass Conference and Exhibition Proceedings, 2023)
As a part of the EU-project “Phy2Climate” an innovative biorefinery is developed and commissioned, which uses contaminated biomass harvested from the pilot sites to produce high quality products. The center of the biorefinery is comprised of an advanced intermediate based pyrolysis process called thermo-catalytic reforming to gain intermediate products like gas, bio-oil, an aqueous phase, and biochar. These intermediates are individually refined. In case of the TCR-gas a purification step is implemented before refinement to reduce the concentration of critical gas components like NH3 and H2S to below 50 ppm. The aqueous phase is purified using an electrochemical process while at the same time producing hydrogen. The purified TCR-gas and the hydrogen from the electrochemical purification is used in a Gas-to-Liquid plant with the aim to produce sustainable fuels through a Fischer-Tropsch-synthesis. The so produced liquid hydrocarbons are distilled to produce gasoline (EN 228) and diesel (EN 590). The bio-oil is also refined by distillation to be used as marine fuel (ISO 8217). The produced biochar is not further refined and directly assessed as a substitute for petroleum-based coke in the copper smelting industry.
CRIS-Team Scopus Importer:2024-12-16
Keywords: biofuel; biorefinery; innovative concepts; polluted soil; thermochemical conversion